Representation of holomorphic functions of many variables by Cauchy-Stieltjes-type integrals - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider functions of many complex variables that are holomorphic in a polydisk or in the upper half-plane. We give necessary and sufficient conditions under which a holomorphic function is a Cauchy-Stieltjes-type integral of a complex charge. We present several applications of this criterion to integral representations of certain classes of holomorphic functions.